Type and location of isocitrate dehydrogenase mutations influence clinical characteristics and disease outcome of acute myeloid leukemia. Issue 5 (May 2013) - Koszarska, Magdalena; Bors, Andras; Feczko, Angela; Meggyesi, Nora; Batai, Arpad; Csomor, Judit; Adam, Emma; Kozma, Andras; Orban, Tamas I.; Lovas, Nora; Sipos, Andrea; Karaszi, Eva; et al.
Abstract Mutations of isocitrate dehydrogenase 1 and 2 (IDH1/2) are genetic alterations in acute myeloid leukemia (AML). The aim of our study was to investigate the frequency and prognostic effect of IDH1/2 mutations together followed by an individual analysis of each substitution in a Hungarian cohort consisting of 376 patients with AML. IDH1mut and IDH2mut were mutually exclusive, detected in 8.5% and 7.5% of cases, respectively. IDH1/2mut was associated with: older age (p = 0.001), higher average platelet count (p = 0.001), intermediate karyotype (p < 0.0001), NPM1mut (p = 0.022) and lower mRNA expression level of ABCG2 gene (p = 0.006). Overall survival (OS), remission and relapse rates were not different in IDH1mut or IDH2mut vs. IDHneg. IDH1mut and IDH2mut were associated differently with NPM1mut; co-occurrence was observed in 14.3% of IDH1 R132C vs. 70% of R132H carriers (p = 0.02) and in 47.4% of IDH2 R140Q vs. 0% of R172K carriers (p = 0.02). IDH1 R132H negatively influenced OS compared to IDHneg (p = 0.02) or R132C (p = 0.019). Particular amino acid changes affecting the same IDH1 codon influence the clinical characteristics and treatment outcome in AML.